Prevalence of previously undiagnosed hypothyroidism in patients with cholelithiasis in a tertiary care center, North-East India - Singha, Debabrata; Pawar, Naresh Manohar; B. J., Prabhu; Kumar, Nitesh; Gopalarathnam, Sankamithra (International Surgery Journal, 2017)
Background: Earlier, the studies had an increased prevalence of previously diagnosed hypothyroidism in gallstone patient and recent studies also demonstrated low bile flow in hypothyroid subjects or the sphincter of oddi expresses thyroid hormone receptors and thyroxin has a direct prorelaxing effect on the sphincter. Iceberg of hypothyroidism was present in cholelithiasis patients. The objective of this study was to find out the prevalence of previously undiagnosed hypothyroidism in cholelithiasis patients. Methods: A prospective study was conducted in the 500 consecutive patients with cholelithiasis between 1st October 2014 and 31st March 2016 to find relation between gallstone and hypothyroidism. Patients already diagnosed as hypothyroidism were excluded. In each patients, detailed history and clinical examination was done and sent for ultrasound of neck for goitre detection and laboratory Thyroid hormone assay (S-FT3, S-FT4 and S-TSH). Results: A total of 2.2%, 5.0% and 6.6% (total 13.8%, 69 of 500) of the cholelithiasis patients were diagnosed to have clinical, subclinical and borderline subclinical hypothyroidism. In women older than 50 year, the prevalence of clinical and subclinical plus borderline-hypothyroidism was 6.8% and 25.6% (11.7%±13.9%) and clinical plus subclinical plus borderline-subclinical hypothyroidism was 32.4% in cholelithiasis patients. Conclusions: Although a low prevalence of hypothyroidism was found in this study, but it is evident that subclinical and borderline subclinical hypothyroidism were significantly more common, compared with the clinical hypothyroidism and with increasing age there was increase in its prevalence, so we recommend that S-TSH level should be measured for every patient with cholelithiasis older than 50 years.